Forensic analysis of Telegram Messenger for Windows Phone - Gregorio, J.; Gardel, A.; Alarcos, B. (Digital investigation, 2017)
This article presents a forensic analysis methodology for obtaining the digital evidence generated by one of today's many instant messaging applications, namely “Telegram Messenger” for “Windows Phone”, paying particular attention to the digital forensic artifacts produced. The paper provides an overview of this forensic analysis, while focusing particularly on how the information is structured and the user, chat and conversation data generated by the application are organised, with the goal of extracting related data from the information. The application has several other features (e.g. games, bots, stickers) besides those of an instant messaging application (e.g. messages, images, videos, files). It is therefore necessary to decode and interpret the information, which may relate to criminal offences, and establish the relation of different types of user, chat and conversation.